2020
DOI: 10.21203/rs.3.rs-52481/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of deep learning with regression analysis in creating predictive models for SARS-CoV-2 outcomes

Abstract: Background: Accurately predicting patient outcomes in SARS-CoV-2 could aid patient management and allocation of healthcare resources. There are a variety of methods which can be used to develop prognostic models, ranging from logistic regression and survival analysis to more complex machine learning algorithms and deep learning. Despite several models having been created for SARS-CoV-2, most of these have been found to be highly susceptible to bias. We aimed to develop and compare two separate predictive model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The C-index showed that the accuracy of the deep-learning model (0.822) was about 4% better than that of the CPH model (0.782). It was indicated that deep learning may be more suitable for handling large samples, multivariate and nonlinear survival analysis than the CPH model, which was consistent with the research results [27][28][29].…”
Section: Discussionsupporting
confidence: 84%
“…The C-index showed that the accuracy of the deep-learning model (0.822) was about 4% better than that of the CPH model (0.782). It was indicated that deep learning may be more suitable for handling large samples, multivariate and nonlinear survival analysis than the CPH model, which was consistent with the research results [27][28][29].…”
Section: Discussionsupporting
confidence: 84%
“…In this context, a major difference between statistical analysis and ML is that the latter often sacrifices interpretability (or explainability) in favor of the model's predictive power (Song et al, 2021b), even though both ML and statistical analysis may perform equally well on some datasets. For example, area under the receiver operation characteristic (AUROC) curves have been compared for models predicting various diseases, revealing values of 0.736 (ML) vs. 0.748 (logistic regression) when predicting acute kidney disease (Song et al, 2021b), 0.837 (neural net models) vs. 0.836 (regression models) when predicting infraction mortality (Piros et al, 2019a), and 0.926 (ANN) vs. 0.869 (Cox regression) when predicting the outcome of COVID-19 (Abdulaal et al, 2020b).…”
Section: Descriptive Modelsmentioning
confidence: 99%
“…Besides, most recent studies have been reported to understand and diagnose the patients with COVID-19 [ 37 42 ] such as temporal deep learning [ 43 ], data-driven based extreme gradient boosting (XGBoost) [ 44 ], deep learning with regression analysis [ 45 ], biomarkers-based [ 46 ], machine learning and clinical data based [ 35 , 47 , 48 ], statistical neural network (NN) and DL [ 49 51 ], boosted random forest [ 52 ], CNN-LSTM, CNN-RNN and CNN-ML based on X-ray images [ 53 – 57 ].…”
Section: Related Workmentioning
confidence: 99%